2015
DOI: 10.2139/ssrn.2618395
|View full text |Cite
|
Sign up to set email alerts
|

Communication Problems? The Role of Parent-Child Communication for the Subsequent Health Behavior of Adolescents

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Important associations were found between characteristics of family relations and OHL in adolescents. The association between high family cohesion ("enmeshed" type) and better levels of OHL has also been reported in a previous study, which found that high family cohesion can influence learning levels among children 19 and that communication between parents and children can affect health-related behaviors in adolescents 20 .…”
Section: Discussionsupporting
confidence: 70%
“…Important associations were found between characteristics of family relations and OHL in adolescents. The association between high family cohesion ("enmeshed" type) and better levels of OHL has also been reported in a previous study, which found that high family cohesion can influence learning levels among children 19 and that communication between parents and children can affect health-related behaviors in adolescents 20 .…”
Section: Discussionsupporting
confidence: 70%